Phytoseiidae (Acari: Mesostigmata) of the subfamily Amblyseiinae from Brazil - Lofego, Antonio Carlos; Barbosa, Marina Ferraz De Camargo; Demite, Peterson Rodrigo; Moraes, Gilberto José De (Zootaxa, 2024)
Phytoseiidae is composed of essentially predatory mites most commonly found on the aerial plant parts. Presently, it is considered to contain about 2,650 valid species, divided into nearly 102 genera of three subfamilies: Amblyseiinae, Phytoseiinae and Typhlodrominae. Approximately 250 of those have been reported from Brazil. Amblyseiinae is the largest subfamily, with about 65% of the described species. This publication summarises the morphologic, taxonomic and distributional information of the Amblyseiinae reported from Brazil, in support of future research on their conservation and practical use. A total of 195 valid species of 29 genera of Amblyseiinae is listed in this publication, 121 of which were described from this country, including seven species which are most certainly incorrect reports, based on the present state of knowledge. Two new combinations are proposed: one in Amblyseius, Amblyseius malvus (Denmark & Evans), and one in Transeius, Transeius piracicabae (Denmark & Muma). Six new synonyms are proposed (Chelaseius lativentris Karg, T. piracicabae, Euseius errabundus De Leon, Typhloromalus clavicus Denmark & Muma, Typhlodromips fordycei (De Leon) and Typhlodromips mangleae De Leon, as senior synonyms of Chelaseius brazilensis Denmark & Kolodochka, Transeius gervasioi Rocha, Silva & Ferla, Euseius plaudus Denmark & Muma, Typhlodromalus simus Denmark & Muma, Typhlodromips igapo Nuvoloni, Lofego, Rezende & Feres and Typhlodromips pederosus El-Banhawy, respectively). A key is provided to help in the separation of the species reported. So far, the most diverse genera in Brazil (followed by the number of species reported) are: Amblyseius Berlese (48), Neoseiulus Hughes (23), Typhlodromips De Leon (22), Iphiseiodes De Leon (14), Amblydromalus Chant & McMurtry (13) and Euseius Wainstein (12). The highest number of species is reported from the southeastern region (119 species), followed by the northeastern (82), the northern (68), the southern (65) and the midwestern (52). The states with highest numbers of registered species are São Paulo (109), Bahia (70), Rio Grande do Sul (62), Amazonas (47), Pernambuco (44) and Minas Gerais (43), while those with lowest numbers are Rio Grande do Norte (16), Sergipe (12), Pará (12), Rondônia (7) and Amapá (5). At least in part, those differences might be related to the dedicated searching effort.